Islamic perspectives of integrating Muslim cemeteries planning with recreational areas in urban setting - Putri Haryati Ibrahim; Ahmad Sarkawi; Mohamed Afla M.R. (Penerbit Universiti Kebangsaan Malaysia, 2022)
The provision of Muslim cemeteries is a requirement stemming from the Quranic teaching that Muslims are buried upon death. Simultaneously, the provision of recreational areas is equally important for a healthy living environment and be part of the ten percent calculation of open spaces required by planning guideline. Due to the scarcity of land particularly in the urban area, one of the ways is to integrate these two types of land uses. This study seeks to examine the Islamic perspective of integrating Muslim cemeteries planning with recreational areas. Using content analysis, Islamic injunctions of the Quran and Hadith were examined together with their exegesis by Muslim scholars. In principle, it is permissible to integrate Muslim cemeteries with the recreational areas provided that their sanctity is preserved. There are limitations of recreational activities that could be done there and only the area with severe land scarcity is allowed to do so. Consequently, a specific planning guidelines for a hybrid cemetery is required as the current GP-010A and GP-005A are standing alone in guiding the cemeteries and open spaces planning respectively. This shariah permissibility based on Maslahah mursalah helps to address the requirement of recreational areas and Muslim cemeteries in an urban setting.